2019
DOI: 10.1002/jso.25521
|View full text |Cite
|
Sign up to set email alerts
|

The impact of unplanned excisions of truncal/extremity soft tissue sarcomas: A multi‐institutional propensity score analysis from the US Sarcoma Collaborative

Abstract: Objective Our aim was to compare outcomes in patients who underwent unplanned excisions (UE) of soft‐tissue sarcomas (STS) against patients with planned excisions (PE). Methods The retrospective 7‐institution US Sarcoma Collaborative database was used. Patients with curative‐intent resection of truncal/extremity STS between 2000 and 2016 were included. Propensity score weighting analysis (PSWA) was performed. Endpoints were locoregional recurrence‐free survival (LRFS), distant metastasis‐free survival (DMFS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…Therefore, in our study, we used the PSM approach for possible confounding factors, which makes the analyses more precise. Compared to other relevant studies (9,20,21,23), the patients included in our study were more likely to have smaller tumor size, and fibrosarcoma and undifferentiated sarcoma were the most common types of histology in our study. Based on our analysis, we found that UPE followed by R0 resection was associated with a better LRFS and 3-year LRFS rates than PE.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, in our study, we used the PSM approach for possible confounding factors, which makes the analyses more precise. Compared to other relevant studies (9,20,21,23), the patients included in our study were more likely to have smaller tumor size, and fibrosarcoma and undifferentiated sarcoma were the most common types of histology in our study. Based on our analysis, we found that UPE followed by R0 resection was associated with a better LRFS and 3-year LRFS rates than PE.…”
Section: Discussionmentioning
confidence: 65%
“…These results might ascribe the poor prognosis in the UPE group to the residual tumor cells contained in muscular or fascial boundaries or fragmented excision (21). However, the findings of subsequent studies were inconsistent with the above conclusions and demonstrated similar or even better LRFS, MFS, and DSS in patients who underwent re-excision than in those with a planned definitive cancer resection as the primary surgical procedure (9,11,13,22). This contradiction in results can be caused by the difficulty in comparing patients who undergo UPE with patients who undergo PE due to the more favorable tumor features and better biological characteristics (such as smaller size, more superficial location, and more benign) of patients with UPE.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, a propensity‐matched study by Zaidi et al showed that unplanned excisions were associated with worse locoregional RFS only in patients with high‐grade tumors. This earlier locoregional recurrence, however, did not translate into earlier distant metastases or worse DSS but could still be associated with added morbidity because of the increased need for re‐excision of local recurrences 18 . The impact of a “watch‐and‐wait” approach after unplanned excisions was evaluated in a 2019 French study, which determined that, although systematic re‐excision offers the best chance at local control (HR, 0.44; P = .01), this does not translate into an improvement in OS, thus observation after unplanned excisions may be a reasonable approach for select patients without macroscopic residual disease or for those who undergo piecemeal excisions during the index operation 59 .…”
Section: Truncal and Extremity Stsmentioning
confidence: 98%
“…Accordingly, referral to a specialized center for further workup should be pursued if a clinical diagnosis of sarcoma is suspected. Although data are currently conflicting regarding the long‐term outcomes of nononcologic, unplanned excisions (see Truncal and Extremity STS, below), there is certainly added morbidity if reresection is needed to achieve negative margins because this may entail a larger procedure than a de novo resection, thus affecting the patient's functional and cosmetic result 16‐18 …”
Section: Pathology Of Stsmentioning
confidence: 99%